18F-methylcholine PET/CT, in vivo magnetic resonance spectroscopy imaging and tissue enzyme biomarkers of choline metabolism in primary brain gliomas. (31st January 2018) - Grech-Sollars, Matthew; Ordidge, Katherine; Vaqas, Babar; Honeyfield, Lesley; Camp, Sophie; Khan, Sameer; Towey, David; Peterson, David; Roncaroli, Federico; O'Neill, Kevin; Barwick, Tara; Waldman, Adam
Abstract: BACKGROUND: Pilot C-11/ F-18 choline PET studies show differential uptake between benign and malignant tumours, however the cellular and molecular basis of this uptake and MRS-visible choline containing compounds (Cho) is not well understood. Choline kinase-α phosphorylates choline, an essential step in membrane synthesis, and is expressed by malignant tumours; it presents a potential novel therapeutic target. We investigate the relationship between choline metabolism detected in vivo using MRS and PET, CKα expression and proliferation in anatomically-defined locations within gliomas. METHOD: Prospective pilot study. 14 patients with suspected primary glioma underwent multimodal 3T MRI (including multi-voxel MRS) and dynamic 18F-FMC PET/CT prior to surgery. Co-registered PET and MRI data were used to identify regions of high and low choline, and targeted biopsies were performed using a surgical planning tool. Immunohistochemistry for CKα expression was performed on these samples. RESULTS: All tumours showed increased tracer uptake relative to contralateral white matter. Significant differences in TBR were found between WHO grade IV and WHO grades I, II & III tumours in 18F-FMC uptake and between WHO grades IV&III and WHO grades I&II using Cho/Cr ratios on MRS. Combining PET and MRS data showed spatial concordance between regions of high PET uptake and highest Cho/Cr ratio, however there was no correlation between the actual levels of uptake (TBR) and the Cho/Cr ratio in these regions. Furthermore, regions of contrast enhancement on MRI showed high uptake on PET. CKα expression assays showed no simple relationship with imaging parameters. CONCLUSION: Combining 18F-FMC uptake and Cho/Cr ratio on MRS may help stratify aggressive glioma phenotypes. Establishing the relationship between imaging-derived choline biomarkers markers and CKα expression is challenging, and may be confounded by both physiological and technical factors.